Precipitation behavior of secondary α phase and mechanical properties of high strength TB9 titanium alloy - HU Ming; QIU Jianke; LEI Xiaofei; ZHANG Jinhu; DONG Limin; YANG Rui (Journal of Aeronautical Materials, 2024)
The precipitation behavior of secondary α phase and mechanical properties of high strength TB9 titanium alloy were investigated during single aging and duplex aging. The alloy phase constitution was analyzed by XRD，and the microstructure was observed by optical microscopy and scanning electron microscopy. The evolution characteristics of the microstructure with aging temperature were mainly analyzed. The room temperature tensile properties and fracture toughness were tested. The research results indicate that during single aging，secondary α phase exhibits serrated and layered precipitation. With increasing aging temperature，the size of α phase increases，and the content of layered α phase increases. The strength at 430 ℃ aging is lower and the plasticity is higher. The strength at 470 ℃ aging is the highest. With increasing aging temperature，the strength first increases and then maintains at the similar level. During duplex aging，most of secondary α phases precipitate in a serrated shape within the grains. With increasing aging temperature，the size of α phase increases，the tensile strength first increases and then decreases，reaching a maximum of 1542 MPa. The tensile strength of duplex aging is significantly higher than that of single aging，which is mainly due to the combined strengthening effect of second phases near grain boundaries and intragranular α phases with serrated shape.